Insulin secretion is increased in non‐diabetic subjects with fasting hypertriglyceridaemia. Issue 3 (11th March 2013) - Simental‐Mendía, Luis E.; Rodríguez‐Morán, Martha; Simental‐Saucedo, Luis; Guerrero‐Romero, Fernando
Abstract: Background: The elevation of triglycerides is strongly linked with insulin resistance, but it has not been evaluated in relationship to insulin secretion. The aim of this study was to determine whether hypertriglyceridaemia is associated with abnormal insulin secretion. Methods: A cross‐sectional study was carried out. Eligible subjects, apparently healthy men and non‐pregnant women aged 20–65 years were recruited. According to the triglyceride levels, subjects were allocated in the groups with hypertriglyceridaemia and normotriglyceridaemia. Hypertriglyceridaemia was defined by serum triglyceride levels ≥150 mg/dL. Insulin secretion was evaluated by the first phase of insulin secretion (1st PIS) and the second phase of insulin secretion (2nd PIS). A regression linear analysis was performed to evaluate the association between hypertriglyceridaemia (independent variable) and the first and second phase insulin secretion (dependent variables). Results: A total of 247 apparently healthy subjects were enrolled; 113 (45.7%) with hypertriglyceridaemia and 134 (54.3%) in the control group. The simple regression linear analysis showed a significant association between hypertriglyceridaemia and the 1st PIS [ B  = 207.0; 95% confidence interval (CI) 33.5–380.5, p  = 0.02] and the 2nd PIS ( B  = 48.7; 95% CI 9.2–88.2, p  = 0.01). A multiple regression linear analysis adjusted by age, sex, body mass index and waist circumference was performed showing that fasting hypertriglyceridaemia remained significantly associated with the 1st PIS ( B  = 184.3; 95% CI 13.0–355.7, p  = 0.03) and the 2nd PIS ( B  = 43.1; 95% CI 4.2–81.9, p  = 0.03). Conclusions: The results of this study show that hypertriglyceridaemia is associated with the increase of the 1st PIS and the 2nd PIS in apparently healthy subjects. Copyright © 2012 John Wiley & Sons, Ltd.